2021
DOI: 10.1186/s12882-021-02594-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial determinants of cardiovascular events among black Americans with chronic kidney disease or associated risk factors in the Jackson heart study

Abstract: Background Individuals with chronic kidney disease (CKD), hypertension (HTN), or diabetes mellitus (DM) are at increased risk for cardiovascular disease (CVD). The extent to which psychosocial factors are associated with increased CVD risk within these individuals is unclear. Black individuals experience a high degree of psychosocial stressors due to socioeconomic factors, environment, racism, and discrimination. We examined the association between psychosocial factors and risk of CVD events am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Although our findings do not substantiate a relationship between John Henryism and cynicism, and subsequently burnout syndrome, they do suggest that there is a genetic component to both outcomes. Research among the general population has shown that hostility is an independent risk factor for cardiovascular disease (Matthews et al, 2004), which has also been reinforced with evidence in population-specific work in African Americans (Bhavsar et al, 2021). Our results suggest that a significant predisposition to hostility and cynicism, when coupled with chronic occupational stress and hostility, could lead to elevated levels of burnout and significant long-term health decline.…”
Section: Discussionsupporting
confidence: 74%
“…Although our findings do not substantiate a relationship between John Henryism and cynicism, and subsequently burnout syndrome, they do suggest that there is a genetic component to both outcomes. Research among the general population has shown that hostility is an independent risk factor for cardiovascular disease (Matthews et al, 2004), which has also been reinforced with evidence in population-specific work in African Americans (Bhavsar et al, 2021). Our results suggest that a significant predisposition to hostility and cynicism, when coupled with chronic occupational stress and hostility, could lead to elevated levels of burnout and significant long-term health decline.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have explored the construction of prediction models for CVD in CKD (15)(16)(17)(18). R. Avram et al conducted a cohort study in which elastic net regression was employed to develop a proteomic risk model for predicting cardiovascular risk among 2,182 participants from a chronic kidney dysfunction cohort (19), with AUC values ranging from 0.84 to 0.89 over 1 to 10 years, yet the clinical model performed poorly, with AUCs between 0.70 and 0.73.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the construction of prediction models for CVD in CKD ( 15 18 ). R. Avram et al.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which increased psychosocial stress burden contributes to clinical outcomes in African Americans with CVD is not fully understood. Carefully designed studies, with rigorous assessment of stressors and stress levels along with robust clinical outcome measures, could be illuminating [ 80 ].…”
Section: The African American Cvd Paradoxmentioning
confidence: 99%